IMPLEMENTASI IMPERATIVE DI PEMERINTAH KOTA BANJAR DALAM RANGKA PENYUSUNAN STRATEGI KEBIJAKAN TEKNOLOGI INFORMASI - Ade Supriatna (STMIK Mardira Indonesia, Bandung, 2015)
Banjar city government of West Java, in carrying out the government has implemented the management of computing, as an aid in the management of the city government administration. However, an assessment of whether the Banjar city government has implemented strategies in the use of information technology, still need more in-depth research and study. Various approaches to the application of information technology to do. But for the early stages necessary to make adjustments to the organizational culture adopted, because the application of information technology is closely related to human resources. There have been many proposed approach to assessing organizational culture, each is seen from different viewpoints. One approach to assessing organizational culture is the Competing Values Framework (CVF). CVF is built based on the reality of what happened in the organization. To assess the organizational culture of the city government of Banjar, can used OCAI (Organizational Culture Assessment Instrument). OCAI instrument in the form of a questionnaire, which must be filled by members of the organization. If we find a source of reference for the government in terms of policy strategy certainly a great deal of information technology. One example of a strategy for information technology policy is applied in the British government, which 8Imperative. But could not categorically be applied in Indonesia, especially in Government Banjar, because the internal and external environment is not the same government. Therefore it is necessary adjustments as needed. Keywords: CVF, OCAI, 8Imperative Abstrak Pemerintah kota Banjar Jawa Barat, dalam melaksanakan manajemen kepemerintahan telah menerapkan komputasi, sebagai alat bantu dalam pengelolaan administrasi pemerintah kota. Akan tetapi penilaian tentang apakah Pemerintah kota Banjar tersebut telah menerapkan strategi dalam penggunaan teknologi informasi, masih perlu penelitian dan pengkajian lebih mendalam. Berbagai pendekatan untuk penerapan teknologi informasi dapat dilakukan. Akan tetapi untuk tahap awal perlu dilakukan penyesuaian dengan budaya organisasi yang dianut, karena penerapan teknologi informasi erat kaitannya dengan sumber daya manusia. Telah banyak pendekatan yang diusulkan untuk menilai budaya organisasi, masing-masing dipandang dari sudut pandang yang berbeda. Salah satu pendekatan untuk menilai budaya organisasi adalah Competing Values Framework (CVF). CVF dibangun berdasarkan realitas yang terjadi di dalam organisasi tersebut. Untuk menilai budaya organisasi Pemerintah kota Banjar, dapat menggukan OCAI (Organizational Culture Assesment Instrument). Instrument OCAI berupa kuisioner, yang harus diisi oleh anggota organisasi. Kalau kita cari sumber acuan bagi pemerintah dalam hal strategi kebijakan teknologi informasi tentunya banyak sekali. Salah satu contoh tentang strategi untuk kebijakan teknologi informasi adalah yang diterapkan di pemerintah Inggris, yaitu 8Imperative. Akan tetapi tidak bisa secara mentah-mentah diterapkan di Indonesia khususnya di Pemerintahan Kota Banjar, karena lingkungan internal dan ekternal pemerintahan tidak sama. Oleh karena itu perlu penyesuaian sesuai kebutuhan. Kata Kunci: CVF, OCAI, 8Imperative